CITY BRANDING VS. CULTURAL BRANDING: TOWARDS A THEORITICAL FOR DEVELOPING BANDUNG IDENTITY - Aldianto, Leo; Budi, Adi Asmariadi; Anggadwita, Grisna; Novani, Santi; Wirawan, Christina (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2019)
City branding is not just an image of the city but also an identity which shows the origin and character of the city. When branding is associated to marketing and advertisement of the city, image/identity shows sovereignty and pride of the city. The transformation of Indonesian government mechanism from centralization to decentralization has brought new sight of government leadership and management. Regional government like city, district, or province has almost full authority on conducting their own government. Bandung city as one of cities in Indonesia has showed its ability on conducting city branding. â€œBandung Juaraâ€ as Bandung city branding could give positive impact on regional economic development through city advertisement. In the other side, the cultural identity of Bandung city does not arise along with those city branding. This study aims to identify the identity of Bandung through city branding compared with cultural branding. This research uses descriptive analysis method by analyzing synthesis literature from some previous researches and related information of Bandung city which collected and summarized to get conclusion about Bandung as branding city vs. culture branding. The finding shows that creativity and modernity are very dominant on Bandung city branding strategy. It gives positive impact on economic development, but in the other side it coversÂ their original culture. Sundanese culture as original culture of Bandung city did not totally supported on city branding strategy. This problem could make Sundanese culture extinct because it will be leaft behind Â and replaced with modern- culture.Keywords: Bandung, city branding, cultural branding, city image, creative city, Sundanese culture